Innovations in Enzyme Technology: Applications in Industry and Medicine - Ali, Mustafa Enaid Kadhim; Abd Ali, Zahraa Abd Al-saheb; Messir, Abbas ayyed kadhim; ganam, Zainab Ali Nazal; Jofan, Adil Saleh Mohammed (American Journal of Biomedicine and Pharmacy, 2024)
Enzymes are biological catalysts that perform specific functions, such as food digestion and synthesis of biomolecules. They have diverse applications in industrial and medical arenas. Many biomolecules can now be synthesized from simple precursors using properly engineered biocatalysts. Since the commercialization of the protease, trypsin, over a hundred years ago, advances in biocatalyst development have accelerated, allowing previously expensive and infeasible biomolecule syntheses to be carried out on increasingly larger scales. The most active research area in enzyme technology is that of enzyme immobilization. The immobilization of enzymes on solid supports, nanoparticles, or within ceramics, fibers, and polymers can improve enzyme stability, target enzymes to specific sites in the body, and reduce enzyme concentrations. This essay attempts to survey the many areas of enzyme technology that have progressed in an incomplete and piecemeal fashion over the past three decades. The rapid expansion of enzyme applications arose from our increased understanding of enzyme structure and function. New technologies introduced in this mid-20th century age of molecular biology made this possible. The exponential increase in our understanding of enzyme structure and function can be shown by the fact that the number of protein-related entries in the public protein databases doubles in number about every 10 years. In 1976, there were only two protein structures solved; in 1986, 89; in 2000, several thousand; in 2007, about 20,000 were known; and in 2012, the PDB had approximately 83,000 protein structures, including those of over 7,500 unique protein sequences. The origin of such an increased number of protein structures is directly linked with technological developments in X-ray crystallography, multidimensional nuclear magnetic resonance spectroscopy, infrared absorption, and imaging techniques, together with early quantum mechanics and quantum chemistry.